Study training intensities variation in the electrical activity of agonist and antagonist muscles in half-back squat test - Altay, Usama (Journal of Physical Education, 2012)
This study aimed to compare and identify the amount of change in the proportions of the difference between the work of front thigh muscles (rectus femoral) and rear (Semitdinosus) for left and right legs and in accordance with the increase in intensities (25% - 50% - 75% - 100%), as well as between right and left legs. Identify differences electric rate achieved when training in these intensities (25% -50% -75%) of the muscles under the electrical signal generated at maximum voluntary contraction (100%) and their conformity with the actual maximal loads. The research sample included four weightlifting age (22) years and a standard deviation (3.464). The researcher used the back squat test (half squat) with intensities (25% -50% -75% -100%) with electrical signal recording (average signal and peak) by (EMG) device type (Myo Trace 400) and electrical signal was analysis by program (Myo Research XP 1.06.67). The researcher used SPSS statistical data to analysis and extracts the results. he concluded that the principle of: the strength of contraction increase with muscle strength and decrease curb of antagonistic muscles assistance, the application is not possible in training in high intensity. And that back and front muscle strength should not exceed 2-3 times or ratio does not exceed (70%). And there is a lack of significant differences in the electrical rectus femoris (front) between left and right legs in high intensities (75-100%), while there were relatively large differences in low intensities (25-50%). The lack of significant differences between the four intensities under discussion (22% -50% -75% -100%) in the average electric and peak of the rectus femoris muscle and Semitdinosus of the two left and right legs .